CULTURE AND PSYCHOLOGY OF PEDAGOGICAL COMMUNICATION - Umedov Shahzod (Scholar Express Journal, 2021)
Communication is a multifaceted process ofdeveloping communication between people based onthe needs of their joint activities. This is one of themost prestigious and influential human actions - toconstantly be in the circle of people and interact withthem. The main goal of the parties involved in arelationship is to achieve mutual understanding andunderstanding. The complexity of this process, ifnecessary "charm", uniqueness is that it is impossibleto find the same language or think and speak thesame way
Keywords: Communication; culture; pedagogy